CONTEMPORARY COSMOLOGY IN DIALOGUE WITH CHRISTIANITY - Ferrao, Victor (Journal of Dharma, 2011)
Contemporary cosmology is evolving by leaps and bounds, and along with it our growing understanding of the universe and the challenge of its integration into our faith is felt with profound clarity. This dialogue is already taking place both in science and in theology. This paper is an attempt to carry further this dialogical process and to respond to this imperative of our faith and to bring about a dialogue with contemporary cosmology and the theology of creation.